Pile Capacity Analysis Using Hydraulic Static Pile Driver and Pile Driver Analysis Test Method on the Tuntang River Bridge Foundation, Grobogan Regency - Al Mukarom, Su'udi; Rochim, Abdul; Astuti, Meilinda Dwi (JACEE (Journal of Advanced Civil and Environmental Engineering), 2025)
Abstract : Results of the analysis of the compressive pile capacity of the HSPD results with PDA-Test (CAPWAP) with The results of the pile capacity analysis using the PDA Test (CAPWAP) obtained an average value of Qult = 480 tons , while the results of the pile pressure capacity analysis using the HSPD Hydraulic Static Pile Driver obtained an average value of Qult = 250.17 Ton so that maximum load on a single pile with a load of Pmax = 225.78 tons / pile. Capacity analysis results from the interpretation value of the compressive pile capacity from the PDA-Test (CAPWAP) with HSPD Hydraulic Static Pile Driver Power support Pile Q ult = 392 Tons at a depth of 28 m from the top of the pile with a pile settlement value of 14.63 mm, so that pile able to support the maximum load on the pile and the settlement is still safe against Pmax settlement value 2.5 cm.